Impact of a fellowship program for faculty development on the self-efficacy beliefs of health professions teachers: A longitudinal study. (27th February 2013) - Singh, Tejinder; de Grave, Willem; Ganjiwale, Jaishree; Supe, Avinash; Burdick, William P.; van der Vleuten, Cees
Abstract : Background : Teachers' belief in their ability to teach influences how much of the new knowledge and skills gained during faculty development (FD) programs are actually implemented at the workplace. Aim : To study the effect of a longitudinal FD program on the self-efficacy beliefs (SEB) of teachers of health professions using quasi-experimental methodology. Methods : The SEB of 70 teachers of health professions enrolling for a longitudinal FD program at three sites in India and one site in South Africa and an equal number of comparable controls were measured using the "teacher efficacy belief systems-self" (TEBS-self) scale. The scale was re-administered at 6 and 12 months to both the groups. Results : Teachers enrolled in the program had lower scores than controls at the beginning of the program but demonstrated a significant increase at 6 months with an effect size of 0.56. The 12-month scores demonstrated a further rise in the participating teachers. The control group maintained the scores but did not show any significant change either at 6 or at 12 months. Conclusion : Longitudinal FD program has positive effect on SEB of teachers.